Antimicrobial activity of a system based on a vegetable extract and three essential oils - Cabrera, Carlos E. (2019)
The objective of the present study was to evaluate the antimicrobial activity of a system obtained, mixing in equal parts, the alcoholic extract of Citrus paradisi seeds, and the essential oils of Luma chequen, Melaleuca alternifolia and Cymbopogon citratus; in front of Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans and Aspergillus niger. Agar well diffusion method was used, considering an inhibition halo of 8 mm, as a minimum valid measure. Individual components showed the following activity (inhibition halo “mm”): C. paradisi extract (E. coli: “9.67 ± 0.47”; S. aureus: “11.67 ± 1.25”; P. aeruginosa: “9.67 ± 0.47”; C. albicans: “7.67 ± 0.47” and A. niger: “no activity”); essential oil of L. chequen (E. coli: “12.00 ± 0.00”; S. aureus: “total inhibition”; P. aeruginosa: “no activity”; C. albicans: “13.33 ± 0,47” and A. niger: “15.33 ± 0.47”); essential oil of M. alternifolia (E. coli: “18.33 ± 0.47”; S. aureus: “total inhibition”; P. aeruginosa: “no activity”; C. albicans: “24.33 ± 1,25” and A. niger: “total inhibition”) and essential oil of C. citratus (E. coli: “no activity”; S. aureus: “no activity”; P. aeruginosa: “no activity”; C. albicans: “No activity” and A. niger: “19.67 ± 0.47”). On the other hand, the proposed system presented the following activity (inhibition halo “mm”): E. coli: “13.00 ± 0.00”; S. aureus: “total inhibition”; P. aeruginosa: “12.33 ± 0.47”; C. albicans: “10.33 ± 0.47” and A. niger: “26.67 ± 0.47”. It is concluded that the proposed system has antimicrobial activity against all the microorganisms evaluated.